Mixing and Switching the Codes in Kindergarten Teachers-Students Interaction: A Case Study at Northern Green School - Melysa, Cici; Pasaribu, Arsen Nahum (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The study of code mixing and code switching has grown in popularity in last decade. The studies of codes on teachers-students interaction, however, were still relatively unexplored. Thus, this study examines code-mixing and code-switching realized in the classroom interaction used by the Kindergarten Teacher in Northern Green School. The study was a qualitative descriptive research using case study. The objective of the study was to analyze the types of the codes and the factors that caused the occurrence of code-mixing and code-switching.Â  The subjects in the study were 2 teachers and 9 students of first level of the Kindergarten. The data were gained through observation and recording. The results showed that the code-mixing and code-switching used by the teachers in the classroom interaction based on the form in many differences, such as code-mixing in the form of insertion, alternation, and congruent lexicalization. While code-switching is in the form of tag switching, inter-sentential switching and intra-sentential switching. The reason of using code-mixing and code-switching in the learning process was due to the conversational habit and the language background of Indonesia language while the school is as a national school plus using English as a means of communication.